Analysis of Macro and Micro Nutrient Intake on Athletes' Physical Fitness at The Student of Sports Atlet - Rina Hasniyati; Hasneli Hasneli; Nabila Fathia Rahmi (Universitas Aisyah Pringsewu, 2023)
An athlete's physical fitness is closely related to his nutritional intake. In 2019, it was found that as many as 27% of athletes in the West Sumatra DISPORA Sports Talent UPTD were in the unfit category. This study aims to analyze the intake of macro and micronutrients on the physical fitness of athletes at the UPTD Sports Talent DISPORA West Sumatra in 2022. The study design was cross-sectional. The population is 140 athletes with a sample of 58 athletes. Sampling using Proportional Random Sampling. Intake data were collected through interviews with the food recall and physical fitness using the bleep test. Data analysis used the chi-square test and logistic regression test. The results of this study indicate that 37.9% of athletes are in the unfit category. Athletes' intake of nutrients that are less than their needs, namely energy (15.5%), protein (8.6%), fat (10.3%), carbohydrates (17.2%), iron (55.2%) vitamins B12 (12.2%), and vitamin C (10.3%). There is no significant relationship between the intake of energy, protein, vitamin B12 and vitamin C with physical fitness, but there is a significant relationship between the intake of fat, carbohydrates and iron with physical fitness. The variable that most affects physical fitness is iron intake. Suggested to increase intake so that athletes' achievements can increase. Suggested to increase intake so that athletes' achievements can increase. Abstrak: Kebugaran jasmani seorang atlet berkaitan erat dengan asupan gizinya. Pada tahun 2019, diketahui bahwa sebanyak 27 % atlet di UPTD Kebakatan Olahraga DISPORA Sumatera Barat berada pada kategori tidak bugar. Penelitian ini bertujuan untuk menganalisis asupan zat gizi makro dan mikro terhadap kebugaran jasmani atlet di UPTD Kebakatan Olahraga DISPORA Sumatera Barat tahun 2022. Desain penelitian adalah cross sectional. Populasi berjumlah 140 atlet dengan jumlah sampel 58 atlet. Pengambilan sampel menggunakan teknik Proportional Random Sampling. Pengambilan data asupan memalui wawancara dengan metode food recall 2x24 jam dan kebugaran jasmani menggunakan bleep test. Analisis data menggunakan uji chi-square dan uji regresi logistik. Hasil penelitian ini menunjukkan bahwa terdapat 37,9 % atlet berada dalam kategori tidak bugar. Asupan zat gizi atlet yang kurang dari kebutuhannya yaitu energi (15,5 %), protein (8,6 %), lemak (10,3 %), karbohidrat (17,2 %), zat besi(55,2 %) vitamin B12 (12,2 %), dan vitamin C (10,3 %). Tidak ada hubungan yang bermakna antara asupan energi, protein, vitamin B12 dan vitamin C dengan kebugaran jasmani, namun ada hubungan bermakna antara asupan lemak, karbohidrat dan zat besi dengan kebugaran jasmani.Variabel yang paling mempengaruhi kebugaran jasmani adalah asupan zat besi. Diharapkan agar atlet lebih memperhatikan asupan agar prestasi atlet dapat meningkat.